Community acquired bacteraemia : a prospective survey of 239 cases - Rayner, Brian L (Department of Medicine, 2017)
The incidence and epidemiology of bacteraemia has been widely reported in the United States and Europe but little data is available from Southern Africa. In addition, most studies have concentrated on the overall incidence of bacteraemia, on individual organisms, or clinical situations, and it is difficult to interpret the data from these studies with regard to community acquired bacteraemia. From a retrospective survey of summaries from a single medical ward at Groote Schuur Hospital it was estimated that bacteraemia accounted for about 4% of the total admissions. It was therefore thought useful to provide clinicians particularly at Groote Schuur Hospital with information about community acquired bacteraemia to improve overall patient management. With this in mind it was decided to undertake a comprehensive prospective study of community acquired bacteraemia at Groote Schuur Hospital.